2016
DOI: 10.1016/j.lfs.2016.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of Src in cancer cell epithelial-to-mesenchymal transition, vascular permeability, microinvasion and metastasis

Abstract: The Src-family kinases (SFKs), an intracellularly located group of non-receptor tyrosine kinases are involved in oncogenesis. The importance of SFKs has been implicated in the promotion of tumor cell motility, proliferation, inhibition of apoptosis, invasion and metastasis. Recent evidences indicate that specific effects of SFKs on epithelial-to-mesenchymal transition (EMT) as well as on endothelial and stromal cells in the tumor microenvironment can have profound effects on tumor microinvasion and metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 160 publications
1
101
0
1
Order By: Relevance
“…Importantly, c‐Src is a critical adaptor protein to modulate focal adhesion molecule responses related with caveolin‐1, paxillin, and p130CAS . These focal adhesion signals are closely associated with metastatic potential of TNBC . How vimentin and c‐Src link together to modulate EMT in TNBC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, c‐Src is a critical adaptor protein to modulate focal adhesion molecule responses related with caveolin‐1, paxillin, and p130CAS . These focal adhesion signals are closely associated with metastatic potential of TNBC . How vimentin and c‐Src link together to modulate EMT in TNBC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells undergoing EMT display low cell surface expressions of E-cadherin, which maintain epithelial connections with neighboring cells, yet they further develop a mesenchymal cell-like cytoskeletal structure, including high levels of vimentin, and acquire the ability to leave the primary tumor mass and invade into surrounding tissues and the circulatory system. 27 There are many factors that contribute to the progression of EMT. One of these factors is hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Together with 12-HETE, it has been found on cancer exosomes, as has c-Src [7, 5455], and the ITGB4 pathway appears to be regulated by micro RNAs such as miR182-5p, which is also predicted to regulate Src [56–58]. These proteins contribute to overlapping networks as well [4], where, for example, MMP9 induction can be seen by Src-mediated or ITGB4/12LOX-mediated signaling [16, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Integrins can be regulated by phosphorylation through the action of the c-Src family kinases (SFKs), non-receptor protein tyrosine kinases that mediate signal transduction during cellular differentiation, adhesion and migration [1618]. Motivated by the observation that integrin β4 has potential tyrosine phosphorylation sites in its cytoplasmic tail, Giancotti et al revealed that β4 functions with SFKs as a binary receptor tyrosine kinase (RTK) that affects both activation and deactivation signals [19].…”
Section: Introductionmentioning
confidence: 99%